2020
DOI: 10.12657/denbio.083.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of climate and air pollution on health status and growth of Picea abies (L.) Karst. peaty forests in the Black Triangle region

Abstract: The Jizerské hory Mts. (the Czech Republic) are part of the Black Triangle region strongly affected by a decline and dieback of Norway spruce (Picea abies [L.] Karst.) stands since the 1970s. In the studied peaty spruce stands in the summit parts of the Jizerské hory Mts., the health status, radial growth and foliar nutrient content in relation to air pollution (SO 2 , NO X and O 3) and climate factors (temperature, precipitation) were investigated in 1960-2015. A considerable disturbance of the stand structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Our results recorded significant correlations with the maximum annual values of SO 2 concentrations in Figure 3 during solar cycle 20 and 23. This period of extremely high mean SO 2 concentrations was characterized by values reaching 57.4 μg•m −3 (maximum daily concentration 1 000 μg•m −3 ) (Vacek et al 2020b), while the limit of vegetation damage according to the Czech Air Protection Act is 20 μg•m −3 . Similarly, in the study area of Broumovsko PLA, diameter increment of Scots pine (Pinus sylvestris L.) was significantly negatively correlated with SO 2 concentrations in the growing season, especially in June-August and on more exposed sites in the 1980s and 1990s (Vacek et al 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Our results recorded significant correlations with the maximum annual values of SO 2 concentrations in Figure 3 during solar cycle 20 and 23. This period of extremely high mean SO 2 concentrations was characterized by values reaching 57.4 μg•m −3 (maximum daily concentration 1 000 μg•m −3 ) (Vacek et al 2020b), while the limit of vegetation damage according to the Czech Air Protection Act is 20 μg•m −3 . Similarly, in the study area of Broumovsko PLA, diameter increment of Scots pine (Pinus sylvestris L.) was significantly negatively correlated with SO 2 concentrations in the growing season, especially in June-August and on more exposed sites in the 1980s and 1990s (Vacek et al 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Reproductive output is also altered by climate and environmental changes (nutritional availability) and many studies have shown that temperature and rainfall can influence reproductive performance [ 9 ]. Many studies have shown that the environment has changed greatly due to the deposition of anthropogenic N, phosphorus (P), and other minerals in the soil and forest stands [ 10 ]. N deposition has increased since the 1900s, having already doubled since then, and is projected to double again by 2050 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cities, air pollution is one of the main problems that affect the biological systems and the quality of residents' life (Lavrov et al 2019;Jaung et al 2020;Lavrov et al 2021a). Aerotechnogenic pollution of the environment through rapid urbanisation that has led to increase in the number of vehicles is one of the strongest factors inhibiting the development of green infrastructure in the city (Fuller and Quine 2016;Ferreira et al 2016;Çelebi and Gök 2018;Grodzinskaya et al 2019;Vacek et al 2020). The negative human impact is manifested in changes in physiological processes, restructuring of links and food chains, destruction of biotic groups, changes in functioning, degradation of natural biotopes and global changes in landscapes and climate (Cuinica et al 2014;Azzazy 2016;Livesley et al 2016;Pietras-Couffignal and Robakowski 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The most dangerous for the green areas of cities are excessive concentrations of aerophytotoxicants NH 3 , NO х (mixture of gases NO, NO 2 , NO 3 ), SO 2 , formaldehyde, phenol, soot and heavy metals. Their sources of entry into the environment are industrial enterprises and motor transport (Nikolaevsky 1998;Miroshnyk 2018;Rao et al 2014;Nowak et al 2014;Vacek et al 2020). Air phytotoxicants cause leaf burns, disruption of physiological processes in plants, toxic and teratogenic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation